1982
DOI: 10.1159/000241580
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Balances in Preterm Infants

Abstract: Zinc balances were studied in three groups of preterm babies. The first group received bank human milk of 25% concentration, the second group bank human milk enriched with 1 g/100 ml of lactalbumin hydrolysate, and the third group an industrial formula in which 40% of the fats were replaced with medium chain triglycerides (MCT). Zn intakes (μg/kg/day) were, respectively, 796 ± 136 (group 1), 689 ± 231 (group 2), and 252 ± 67 (group 3). In all 3 groups, fecal Zn excretion was very high: range; 6,862–635 μg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…These findings are similar to our previously reported results comparing PF and F-PTHM (12), and are consistent with the data of Mendleson et al (2 1) and Tyrala (22). Our data are also in agreement with the observation by Voyer et al (20) that net zinc balance became positive when net fat and nitrogen absorption exceeded 90%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to our previously reported results comparing PF and F-PTHM (12), and are consistent with the data of Mendleson et al (2 1) and Tyrala (22). Our data are also in agreement with the observation by Voyer et al (20) that net zinc balance became positive when net fat and nitrogen absorption exceeded 90%.…”
Section: Discussionsupporting
confidence: 93%
“…Inasmuch as increments in body wt should be associated with zinc and copper accretion, the significant correlation with average daily wt gain seems appropriate. A significant correlation between net zinc balance and net fat and nitrogen absorption has been described (20). In addition, because most of the measures of zinc and copper availability were related to fat excretion (Table 6), and because pasteurization of human milk significantly decreases fat absorption in VLBW infants (36), the use of pooled pasteurized human milk might contribute to the prolonged period of negative net zinc and copper balance described by some investigators (18,19,22).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The lack of correlation between the amount of absorbed zinc and the endogenous fecal zinc, a relationship observed in both normal adults and infants (19 -21), suggests some inefficiency. For example, fat malabsorption has been associated with excessive excretion of endogenous fecal zinc (12), and with negative zinc balance in preterm infants (22).…”
Section: Discussionmentioning
confidence: 99%
“…A total of fourteen studies on zinc retention were identified [11,[17][18][19][21][22][23][24][25][26][27][28][29][30] with data on forty-five distinctly identifiable groups (Tables 1 and 2). All studies were identified in the primary PubMed search.…”
Section: Zincmentioning
confidence: 99%